The Endophytic Strain Trichoderma asperellum 6S-2: An Efficient Biocontrol Agent against Apple Replant Disease in China and a Potential Plant-Growth-Promoting Fungus - Haiyan Wang; Rong Zhang; Yanan Duan; Weitao Jiang; Xuesen Chen; Xiang Shen; Chengmiao Yin; Zhiquan Mao (Journal of Fungi, 2021)
A study was conducted for endophytic antagonistic fungi obtained from the roots of healthy apple trees growing in nine replanted orchards in Shandong Province, China. The fungi were assessed for their ability to inhibit Fusarium proliferatum f. sp. malus domestica MR5, a fungal strain associated with apple replant disease (ARD). An effective endophyte, designated as strain 6S-2, was isolated and identified as Trichoderma asperellum. Strain 6S-2 demonstrated protease, amylase, cellulase, and laccase activities, which are important for the parasitic and antagonistic functions of pathogenic fungi. The inhibition rate of 6S-2 against Fusarium proliferatum f. sp. malus domestica MR5 was 52.41%. Strain 6S-2 also secreted iron carriers, auxin, ammonia and was able to solubilize phosphorus. Its fermentation extract and volatile substances inhibited the growth of MR5, causing its hyphae to twist, shrink, swell, and rupture. The antifungal activity of the 6S-2 fermentation extract increased with increasing concentrations. It promoted the production and elongation of Arabidopsis thaliana lateral roots, and the strongest effects were seen at a concentration of 50 mg/mL. A GC-MS analysis of the 6S-2 fermentation extract and volatile substances showed that they comprised mainly alkanes, alcohols, and furanones, as well as the specific volatile substance 6-PP. The application of 6S-2 spore suspension to replanted apple orchard soils reduced plant oxidative damage and promoted plant growth in a pot experiment. Therefore, the endophytic strain T. asperellum 6S-2 has the potential to serve as an effective biocontrol fungus for the prevention of ARD in China, and appears to promote plant growth.